FERMENTASI ANGGUR (WINE) DARI MANGGA KUWINI (MANGIFERA ODORATA) MENGGUNAKAN SACCHAROMYCES CEREVISIAE - Margaretha Maria Stephanie; Tjandra Pantjajani; Mangihot Tua Goeltom (Perpustakaan Universitas Surabaya, 2018)
Kuwini mango (Mangifera odorata) is a fruit that has a fibrous fruit flesh and flavorful seared so far underutilized. Wine mango Kuwini is one way to increase the economic value and utilization of mango Kuwini, as well as increasing the diversity of food products. In this study Kuwini mango meat processed into juice mango mangoes Kuwini by comparison Kuwini: water 1:2. Granulated sugar is added to the variation of 0%, 5%, 15% and 25%. The results showed that the addition of sugar at the beginning of the fermentation of wine can increase the levels of ethanol in wine Kuwini mango, mango wine Kuwini thus meet the Indonesian National Standard (SNI). Wine mango Kuwini with a difference of optimum increase in the ethanol content is the addition of sugar as much as 15%, with an increase in ethanol content of 8.47%. It also observed changes in total sugar, reducing sugar, total acid tertitrasi (TAT), pH, ethanol and Saccharomyces cerevisiae cell count before and after fermentation. The test results of microbial contaminants Salmonella sp. and coliforms were negative, and a test of the total number of bacterial contaminants are below the maximum contaminant limit (<1 × 102). The test results hedonic / A indicates that the mango wine Kuwini with the addition of 25% sugar has the highest preference level compared with mango wine Kuwini with the addition of sugar 0%, 5% and 15%.